2019
DOI: 10.1353/lan.2019.0053
|View full text |Cite
|
Sign up to set email alerts
|

A unified account of conditioned phonological alternations: Evidence from Guébie

Abstract: This article expands on cophonologies by phase, a model of the interface between morphology and phonology, which was introduced in Sande & Jenks 2018. The crucial innovation of cophonologies by phase is the enhancement of lexical or vocabulary items to include morpheme-specific constraint weights. These weights modify the default phonological grammar of the language only in the domain of evaluation that contains the triggering morpheme, where domains are determined by syntactic phase boundaries. The interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 76 publications
0
43
0
Order By: Relevance
“…When one is present on its own, there is no surface effect. See Sande (2019) for an analysis of a similar doubly conditioned process in Cophonologies by Phase, which we expect could straightforwardly extend to these additional Dogon languages. the tonal requirements of the higher modifier are suppressed (60c).…”
Section: (59)mentioning
confidence: 88%
See 2 more Smart Citations
“…When one is present on its own, there is no surface effect. See Sande (2019) for an analysis of a similar doubly conditioned process in Cophonologies by Phase, which we expect could straightforwardly extend to these additional Dogon languages. the tonal requirements of the higher modifier are suppressed (60c).…”
Section: (59)mentioning
confidence: 88%
“…traditional gang effects in weighted constraint models, for example, in Shih (2016)), such that only when two specific morphemes are present in a single phase do we see some alternation. (See Sande (2019) for an example of this kind of doubly morphologically conditioned phonological alternation analyzed in CBP.) Alternatively, two morphemes might adjust distinct constraints such that when each one individually is present, we see a distinct phonological effect; however, when both are present, the morpheme-specific effects compete for dominance.…”
Section: Constraint Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…I show that CBP can straightforwardly model a range of phonological processes that require at least two morphological triggers. As with phonology across words or in sub-word domains (Sande 2019a, Sande et al 2020, the domain of morphologically conditioned phonology with two triggers appears to be related to syntactic phase boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…When there is not, I adopt the widely accepted view that at least D, Voice and C are phase heads. 1 Previous work in CBP has shown that it can model a wide range of phenomena, including phrasal or cross-word phonology triggered by specific morphemes, as well as category-specific phonology (Sande & Jenks 2018, Sande et al 2020 and long-distance harmony and tone-spreading processes whose scope is limited by syntactic boundaries (Sande 2019a), as well as local morphologically conditioned phonology (Sande 2019a, Sande et al 2020. Work in progress (Jenks 2018, Baron 2019) also shows that Cophonologies by Phase can account for syntax-prosody interaction without requiring a separate step of syntax-to-prosody mapping in the grammar.…”
Section: Introductionmentioning
confidence: 99%